2012
DOI: 10.1111/j.1556-4029.2011.02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of False Allegation Adult Crimes

Abstract: The purpose of this study was to identify common factors in false allegation adult crimes, by examining the dynamics involved in 30 confirmed false allegation cases. The authors conducted a comprehensive review of these adjudicated cases and then completed a collection instrument to capture offender demographics, offense characteristics, and motive. The results indicated that most false allegation crimes were committed by women (73.3%) and Caucasians (93.3%). Data indicated that more interpersonally violent al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…The three major categories of alibi, revenge, and sympathy or attention were also found by other researchers (McNamara, McDonald, & Lawrence, 2012 ). McNamara et al studied 30 false allegations that were submitted by other law enforcement agencies to the Federal Bureau of Investigations’ (FBI) National Center for the Analysis of Violent Crime (NCAVC) during a 15-year period.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The three major categories of alibi, revenge, and sympathy or attention were also found by other researchers (McNamara, McDonald, & Lawrence, 2012 ). McNamara et al studied 30 false allegations that were submitted by other law enforcement agencies to the Federal Bureau of Investigations’ (FBI) National Center for the Analysis of Violent Crime (NCAVC) during a 15-year period.…”
Section: Introductionsupporting
confidence: 82%
“…The difference, however, is that revenge, an alibi, and attention or sympathy are emotional gains while a motive like a promotion to a better job is more a material gain. McNamara et al ( 2012 ) also reported that some complainants were motivated by profit, i.e., material gain. But there are still other motives for a complainant to file a false allegation.…”
Section: Introductionmentioning
confidence: 99%
“…102 This echoes the wider literature which suggests that many false accusers are vulnerable in the sense of being young 103 or suffering from mental health problems, 104 Munchausen by Proxy, 105 learning disabilities, 106 or narcotic addiction. 107 In their analysis of 30 cases involving false allegations, McNamara et al found false claims were made in relation to a range of criminal offences 108 and resulted from such factors as mental illness and financial problems. Both males and females also made false allegations to gain 'attention and sympathy.'…”
Section: How Common Are False Allegations?mentioning
confidence: 99%
“…In their analysis of 30 cases of false allegations, McNamara et al found false claims were made in relation to a range of criminal offences. They also found that the allegations resulted from such factors as mental illness and financial problems. Both males and females made false allegations in order to gain ‘attention and sympathy.’ Such people, they argue ‘utilise an event they believe will yield the strongest response from others.’ They note that the types of offences which attract false complaints differ, to some degree, between men and women.…”
Section: The Question Of False Allegationsmentioning
confidence: 99%
“…In their analysis of 30 cases of false allegations, McNamara et al found false claims were made in relation to a range of criminal offences. 70 They also found that the allegations resulted from such factors as mental illness and financial problems. Both males and females made false allegations in order to gain 'attention and sympathy.'…”
Section: The Question Of False Allegationsmentioning
confidence: 99%